2020
DOI: 10.1038/s41598-020-68612-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of potent bifunctional β-lactam- and homoserine lactone-degrading enzymes from marine microorganisms

Abstract: Genes that confer antibiotic resistance can rapidly be disseminated from one microorganism to another by mobile genetic elements, thus transferring resistance to previously susceptible bacterial strains. the misuse of antibiotics in health care and agriculture has provided a powerful evolutionary pressure to accelerate the spread of resistance genes, including those encoding β-lactamases. These are enzymes that are highly efficient in inactivating most of the commonly used β-lactam antibiotics. However, genes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…BJP-1 is a new Subclass B3 metallo-lactamase (MBL) that was discovered in Bradyrhizobium japonicum, a nitrogen-xing bacteria used in agriculture, whose genome was recently sequenced [41,42] . BJP-1 is a chromosomally encoded intrinsic MBLs that may not acquire through horizontal gene transfer [43,44] . In this study, the BJP-1 gene was found in nearly 11% of the assemblies, implying that it was transferred from soil microbiota to humans.…”
Section: Discussionmentioning
confidence: 99%
“…BJP-1 is a new Subclass B3 metallo-lactamase (MBL) that was discovered in Bradyrhizobium japonicum, a nitrogen-xing bacteria used in agriculture, whose genome was recently sequenced [41,42] . BJP-1 is a chromosomally encoded intrinsic MBLs that may not acquire through horizontal gene transfer [43,44] . In this study, the BJP-1 gene was found in nearly 11% of the assemblies, implying that it was transferred from soil microbiota to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The MVs of both strains contained a sufficient amount of the enzyme to degrade the antibiotic in the cultivation medium and permit the growth of the ampicillin susceptible E. coli. We postulate that it may be an important mechanism of Pectobacterium success in various habitats as some β-lactamases are able to degrade lactone rings [41,42], and N-acyl homoserine lactones (AHLs) are signalling molecules in the quorum sensing mechanism. The quorum sensing mechanism plays an essential role in Pectobacterium virulence and controls the expression of PCWDEs [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…This similarity challenges the classification of the serine-dependent enzymes and the metal-dependent enzymes found in marine bacteria. When such enzymes are purified and annotated as β-lactamases (and often as having an ancient heritage) [ 148 , 149 , 150 , 151 , 152 ], is the basis for their heritage that of β-lactam resistance or that of quorum quenching [ 153 ]? Selleck et al suggest credibly that lactonase/lactamase promiscuity may offer an evolutionary advantage [ 153 ].…”
Section: Does the Marine Environment Contain β-Lactam-degrading Enzymes?mentioning
confidence: 99%